(untitled) (LEARNing Landscapes, 2017)
Trauma affects our classrooms frequently. Children who observe or experience trauma directly often demonstrate an altered learning process and shifting emotional needs. What guidance might inform K-12 instruction productively? This article frames the patterns discovered when a teacher researcher studied the teaching practices, strategies, and language of six educators who survived their own experiences of childhood sexual assault. With a keen awareness on strength and fragility, I detail the engaging, authentic, and community-centered methods from educators who turned their own experiences of trauma into effective ways to engage learners and build welcoming learning communities.